Postoperative treatment of intermediate-risk early stage cervical cancer: results of a survey from the Gynecology Study Group in the AIRO Gyn and MITO Groups. (June 2022) - Perrucci, Elisabetta; Cerrotta, Annamaria; Macchia, Gabriella; Augurio, Antonietta; Campitelli, Maura; De Sanctis, Vitaliana; Lazzari, Roberta; Magri, Elena; Marsella, Anna Rita; Meregalli, Sofia; Tamburo, Marinella; Ferrandina, Gabriella; et al.
Abstract: This survey investigated prognostic factors, treatment modalities, references followed and radiation oncologists' opinions to prescribe adjuvant therapy in early intermediate-risk cervical cancer. All but one recommended pelvic radiotherapy ± vaginal boost (45%) with or without chemotherapy (20%). 88% believed other prognostic factors could integrate classic risk criteria. 66% considered chemo-radiation indicated in case of lymphovascular invasion and suboptimal node dissection, high grade, size ≥ 4 cm, non squamous histology and risk factors combination. This wide heterogeneity of treatments reflects the different guideline options due to the lack of defined indications. The need of integrating the classic prognostic factors with others factors was unanimously expressed by radiation oncologists. The best local and systemic therapy should be established through new studies. These results highlighted the need of a position paper to standardize adjuvant treatment in Italy and to design collaborative studies to clarify the controversial aspects. Graphical Abstract: ga1 Highlights: Different risk classifications and adjuvant treatments were used. Different indications across the guidelines determined the range of options. Other risk factors should be further investigated to define risk classification. Role of chemoradiation in intermediate risk disease should be clearly established.